Spectrum of histopathological findings in pediatric renal biopsies; a five-year single center experience in Egypt - Wael Mostafa Hamza; Ahmed Fayed; Amr Mohamed Shaker; Mahmoud Mohamed El Nokeety (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Medical renal diseases stand as one of the major health problems in pediatric age group considering its morbidity/mortality and the subsequent management plans. Objectives: In this manuscript, the spectrum of histopathological patterns of medical nephropathic lesions in Egyptian pediatric patients over duration of five years is reported with clinical indications. Patients and Methods: We conducted a retrospective study for analysis of our pathological reports of renal needle biopsies during the period from January 2014 until January 2019. One hundred and sixteen cases were included. Results: The most commonly encountered pediatric renal pathology was minimal change disease (27.59%), followed by congenital glomerular diseases (22.41%), focal segmental glomerulosclerosis (12.93%), and thrombotic microangiopathy (7.76%). The most common clinical indication for biopsy was nephrotic syndrome (37.07%) followed by impaired renal functions with elevated serum creatinine (21.55%). In addition, we report very rare histological findings in few cases including infantile nephropathic cystinosis, Barakat syndrome and C3 glomerulopathy. Conclusion: Minimal change disease and congenital glomerular diseases accounted for half of pediatric renal pathologies in the study population. The most common clinical indication for renal biopsy was nephrotic syndrome. Electron microscopic examination and genetic studies are mandatory for proper evaluation of pediatric nephropathies.